Patagonia as the Land of Possibilities: the Gentle Land by Elpidio Isla (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
This paper analyzes a fragment of the novel The Gentle Land by Elpidio Isla, an author from Santa Cruz province in Argentina. The text shows how the Patagonia environment enables the fictionalized historical character,  Simon De Alcazaba,  to acquire self-knowledge.The reason for the journey as well as his approaching death lead the protagonist to redefine his life and it's underlying values. In that far-off southern land,  where he was unable to implement the schemes that Western Imperial reason had plotted to justify its expansion,  the character not only understands the true meaning of his life,  but it's also able to retell it.